2018
DOI: 10.3389/fpls.2018.00894
|View full text |Cite
|
Sign up to set email alerts
|

Highly Disturbed Populations of Seagrass Show Increased Resilience but Lower Genotypic Diversity

Abstract: The response of seagrass systems to a severe disturbance provides an opportunity to quantify the degree of resilience in different meadows, and subsequently to test whether there is a genetic basis to resilience. We used existing data on levels of long-standing disturbance from poor water quality, and the responses of seagrass (Zostera muelleri) after an extreme flood event in Moreton Bay, Queensland, Australia. Sites were grouped into high and low disturbance categories, in which seagrass showed high and low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 54 publications
1
17
1
Order By: Relevance
“…Overall, our results suggest that ongoing eutrophic conditions in the Gulf of Pozzuoli are weakening the local P. oceanica meadow, since these plants showed the greatest percentage of mortality, particularly under increased temperature. Our findings do not seem to be a general rule for seagrasses, since Connolly et al (2018) found the opposite trend in Z. muelleri. In that study, plants growing in more disturbed sites were more resilient to further disturbance, although with a lower genotypic diversity, suggesting a genotypic selection.…”
Section: Discussioncontrasting
confidence: 91%
“…Overall, our results suggest that ongoing eutrophic conditions in the Gulf of Pozzuoli are weakening the local P. oceanica meadow, since these plants showed the greatest percentage of mortality, particularly under increased temperature. Our findings do not seem to be a general rule for seagrasses, since Connolly et al (2018) found the opposite trend in Z. muelleri. In that study, plants growing in more disturbed sites were more resilient to further disturbance, although with a lower genotypic diversity, suggesting a genotypic selection.…”
Section: Discussioncontrasting
confidence: 91%
“…Seagrasses often exist as natural monocultures and, therefore, make ideal model systems to test ecological and population genetic hypotheses. This model has proved informative in both population dynamic 11,73,74 and population genetic studies 39,66 but these are rarely linked. In this study, we estimated a suite of common genetic and genotypic diversity parameters amongst Zostera marina populations exhibiting a range of long-term population trajectories.…”
Section: Resultsmentioning
confidence: 99%
“…Under extreme high levels of disturbance, the majority of genets can be removed from a location, leading to very low clonal richness 65 . Regular disturbance events have also been linked with low levels of clonal diversity in tropical seagrasses, whereas less frequent disturbance had no effect 66 , suggesting some threshold effect in a species’ ability to resist loss of genetic diversity (see also 39,40 ). Old Grimsby Harbour is clearly impacted by damage to the seabed, which provides external forcing of the spatial pattern of seagrass – essentially large holes in previously more uniform vegetation 59 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, shoalgrass meadows have varying levels of population connectivity due to the physical isolation of the shallow embayments and lagoonal habitats where most meadows are located (Handley, Altsman, & DeMay, 2007). Thus, the morphological attributes of the two populations could be related to the level of genetic diversity derived from a population's degree of isolation (Connolly et al, ; Diekmann et al, ). Future transplant experiments should include sampling of donor genetics to determine the relative influence of genetic diversity on any connection between morphological features and transplant resilience.…”
Section: Discussionmentioning
confidence: 99%